2019
DOI: 10.1002/csr.1820
|View full text |Cite
|
Sign up to set email alerts
|

Does financial availability sustain financial, innovative, and environmental performance? Relation via opportunity recognition

Abstract: Traditionally, firms tend to incline toward financial performance and profitability to surge shareholder's wealth. In the modern day, in addition to financial performance, innovative and environmental performance has also become a central effort. However, all firms are not flourished in the achievement of financial, innovative, and environmental performance, particularly small‐ and medium‐sized enterprises (SMEs), which need adequate financial resources due to lack of resources and can search for opportunities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(64 citation statements)
references
References 81 publications
1
48
0
Order By: Relevance
“…Our findings match several studies which have scrutinized a significant positive association between FL and sustainable competitive performance [51,56] and innovative performance [122]. Consistent with Memon, Yong and Memon [123] who revealed that financial literature managers have high capabilities of exploiting new opportunities and generating new ideas that are very helpful for high performance.…”
Section: Discussionsupporting
confidence: 91%
“…Our findings match several studies which have scrutinized a significant positive association between FL and sustainable competitive performance [51,56] and innovative performance [122]. Consistent with Memon, Yong and Memon [123] who revealed that financial literature managers have high capabilities of exploiting new opportunities and generating new ideas that are very helpful for high performance.…”
Section: Discussionsupporting
confidence: 91%
“…It is doubtless that intangible resources are essential for SMEs' growth and survival in transition and emerging economies. However, mere intangible resources do not boost operational activities of SMEs, they must have satisfactory finance to recognize new opportunities to enhance their innovative and financial performance [79]. The efficient use of financial resources saves ventures from wastage of capital in different investment activities and enables firms to utilize the resources properly [80].…”
Section: The Moderating Role Of Financial Resourcesmentioning
confidence: 99%
“…financial resources indicate a firm capacity to have finance and capital to be used for the smooth running of operational activities. To measure FA, we used five items adopted from the prior study Memon, An and Memon [79].…”
Section: Measurement Of Variablesmentioning
confidence: 99%
“…Additionally, environmental and social activities need adequate financial resources (Memon et al, 2020) and many organizations due to limited financial resources do not participate in volunteer activities (Danso et al, 2019). Hence, we believe that the endeavour is cherished to test if government incentives motivate NPOs toward SDGs.…”
Section: Introductionmentioning
confidence: 99%